Development of a simple and quick immunochromatography method for detection of anti-HPV-16/-18 antibodies. - Fumiko Endo; Tsutomu Tabata; Daichi Sadato; Machiko Kawamura; Noriyuki Ando; Keisuke Oboki; Masako Ukaji; Kaoru Kobayashi; Yukuharu Kobayashi; Tomoaki Ikeda; Futoshi Shibasaki (PLoS ONE)
Immunochromatography (IC) is widely used to detect target molecules in biological fluids. Since this method can be performed without a special technique or device, IC is a convenient way to assess the existence of antibodies or pathogens such as viruses and bacteria, simply and quickly. In this study, we established an IC method to detect serum antibodies against oncogenic human papillomavirus (HPV)-16 and HPV-18 L1 proteins using recombinant L1 proteins produced by silkworms as antigens. Infection of oncogenic HPVs is a major risk factor of cervical cancer, which is one of the most common cancers in women worldwide. We first measured blood sera of two groups by magnetic beads enzyme-linked immunosorbent assay (MB-ELISA). For the first group, sera were collected prospectively from young women who planned to receive HPV vaccination. The second group consisted of children under 20 years of age, non-vaccinated healthy women, vaccinated healthy women, dysplasia, cervical intraepithelial neoplasia III, and cervical cancer patients. We confirmed that standard vaccination doses significantly increased serum HPV antibody concentrations, and the level was sustained at least more than 30 months after vaccination. In contrast, an increase in antibody concentration was not observed in patients with precancerous cervical changes and cervical cancer. We next measured the samples in both groups using the IC method we originally developed, and found that the measurement values of IC highly correlated with those of MB-ELISA. The simple and quick IC method would be a useful tool for rapid monitoring of L1 specific antibody levels in a non-laboratory environment. With less than one drop of serum, our IC can easily detect serum HPV-16/-18 antibodies within 15 minutes, without the need for electronic devices or techniques.